Study on the making of chip with laksa leaf taste - Arfian Saputra; Terip Karo-Karo; Sentosa Ginting (Jurnal Rekayasa Pangan dan Pertanian, 2013)
Laksa leaf is just used as vegetable, so that a processing is needed in order to increase its value added. Usual food processing using laksa leaf is sour vegetable. The laksa leaf is useful as antioxidan. The research was done to find ratio of tapioca flour with wheat flour and concentration of laksa leaf to produce chip. The research had been performed using completely randomized design (CRD) with 2 factors, i.e : the ratio of tapioca flour with wheat flour (T) : (100:0, 80:20, 60:40, 40:60) and concentration of laksa leaf (D) : (0%, 9%, 18%,  27%), Parameters analyzed were moisture content, ash content, fat content, fiber content, the expansion degree and organoleptic values (colour, aroma, taste, texture). The results showed that the ratio of tapioka flour with wheat flour had highly significant effect for all the parameters. The laksa leaf concentration had highly significant effect for all the parameters except expansion degree. The interaction between the two factors had highly significant effect on moisture content, fat content, organoleptic values and texture, had significant effect on ash content  and had no effect on   fiber content, expansion degree, colour and aroma. . Keywords : tapioka flour, wheat flour, laksa leaf, chips